Virtual Porous Carbons - Terzyk, A.; Furmaniak, S.; Gauden, P.; Harris, P.; Kowalczyk, Piotr (Elsevier, 2012)
This chapter reviews results obtained using virtual porous carbon (VPC) models associated with molecular simulation techniques. By discussing different examples, we try to demonstrate that this can be a really helpful approach in adsorption science. At the start of the chapter, we briefly describe the concept of VPC, the methods of absolute pore-size distribution determination, and the so-called virtual oxidation technique – the procedure of surface oxygen groups addition. Next, we briefly provide details of two molecular simulation techniques applied by us namely the grand canonical Monte Carlo and molecular dynamics techniques. Major attention is paid not only to the simulation techniques but also to applied models and the values of the parameters used. Finally, we discuss the results of simulation on VPC. This part is divided into five major subparts. We show the application of VPC and molecular simulations for: (i) checking the reality of carbon PSD determination methods (based on adsorption data of noble gases), (ii) testing the reality of carbon PSD determination methods (based on adsorption data of gases having permanent electric moments), (iii) testing the reality of methods providing the average micropore diameter and the reality of the BET surface area, (iv) searching the meaning of empirical parameters, and (v) explaining experimental regularities. Finally, some limitations and perspectives are discussed.